As (im)possibilidades de responsabilização penal da Rússia perante a grave e generalizada violação de direitos no conflito internacional contra a Ucrânia - Pacheco, Giorgio Moro (2024)
This monographic work deals with the possibilities or impossibilities, as well as the ways in which criminal liability can be attributed to Russia for the serious violation of human rights in Ukraine. The conflict has its origins during the period of the low middle ages, a period when both States were one. However, over the centuries, there were several historical, political and social factors that awakened patriotic feelings in the Ukrainian people and the need for independence from Russia. However, if on one side there was the desire for independence, on the other there was the need for control, whether of the people or the territory. Based on a discourse of denazification and demilitarization of Ukrainian territory, the Russian invasion of Ukraine begins in February 2022. In this way, as with any conflict, whether international or not, it is necessary to seek accountability for those who violate rights and rules of international law. To this end, in order to protect and ensure rights that are violated, or about to be violated, as well as punish the aggressor, it is extremely important to analyze factors such as competence and effectiveness of some of the main Courts, as well as Courts of the current system of protection of rights on the international scene. In a first and general analysis, it is inferred that the International Criminal Court, the European Court of Human Rights and the International Court of Justice may have jurisdiction, but come up against possible incompetence, whether material or not, in the international conflict. . It is also worth thinking about the possibility of establishing exceptional courts or applying the principle of universal jurisdiction in the face of possible incompetence of the Courts or Tribunals analyzed. The present work uses the deductive method of procedure and analysis and the legal-bibliographical research technique, supported by national and international instruments.